Leveraging internal curing effect of fly ash cenosphere for alleviating autogenous shrinkage in 3D printing. (5th September 2022) - Tao, Jie-Lin; Lin, Can; Luo, Qi-Ling; Long, Wu-Jian; Zheng, Shu-Yi; Hong, Chen-Yu
Graphical abstract: Highlights: Perforated fly ash cenospheres (PFACs) were used as an internal curing agent for developing printable cement-based materials. Internal curing effect of PFACs can alleviates autogenous shrinkage strain by 81% in 3D printing component. Effect of PFACs on the rheology of limestone calcined clay cement (LC3) was evaluated. Fiber Bragg Grating technology was adopted to study autogenous shrinkage by monitoring the interlayer strain. Incorporating 15 vol% PFAC to replace sand gives LC3 exceptional resistance to autogenous shrinkage and printability. Abstract: The development of three-dimensional (3D) printing technology in the construction industry has coincided with growing attention on the investigation of printable cement-based composite. Meanwhile, the exploitation of high-performance and environmentally friendly printable cement-based composite is an inevitable path for the sustainable development of 3D printing in the construction industry. This study proposes the use of perforated fly ash cenospheres (PFACs) as internal curing (IC) agent into limestone calcined clay cement (LC3) mortar to develop a novel green printable cement-based composite. Rheological behavior of LC3 mortar containing PFACs has been shown to meet the requirements of 3D printing. The internal curing effect on autogenous shrinkage of mortar was studied by employing Fiber Bragg Grating (FBG) technology. Compressive and flexural strengths of LC3 mortar containing PFACs were evaluated. Additionally, microstructural investigation was analyzed through SEM, and the hydration products were studied by XRD and TG tests. Results suggest that shrinkage strain of LC3 mortar containing 15% PFAC was approximately 80% lower than that of mortar without PFAC, which indicates that PFAC in LC3 mortar can be effective in holding the mixing water for IC that can reduce the autogenous shrinkage. Furthermore, additional mechanical strength of mortar containing PFAC was generated through IC effect and the pozzolanic activity of PFAC, which can effectively compensate the strength loss caused by the PFAC. However, microstructural investigation indicated that the pozzolanic activity of PFAC has limited effect on cement hydration compared with the introduction of additional IC water. Consequently, this study reveals that it is effective to adopt PFAC as IC agent into LC3 mortar to develop high-performance and sustainable printable cement-based composite.